The effect of ZrO2 nanoparticles on mechanical property and dielectric respond of CaCu3.1Ti4O12.1 ceramics - Chompoonuch Puchmark (2018)
Giant dielectric CaCu3.1Ti4O12.1based composites containing nanoparticles of ZrO2were synthesized using a conventional mixed oxide method. Then properties of the nanocomposites were characterized using a variety of methods. The addion of ZrO2inhibited grain growth and changed the mode of fracture from a partially inter-granular in pure CaCu3.1Ti4O12.1to a mostly intra-granular fracture in the composite samples. The nanocomposites also exhibited a frequency stability of the dielectric constant and a low tangent loss (0.06) at 3-9 kHz. The hardness and dielectric results are also discussed and related to the microstructure. Copyright © Taylor &Francis Group, LLC.